Altered Neurovascular Coupling in Unilateral Pulsatile Tinnitus - Li, Xiaoshuai; Xu, Ning; Dai, Chihang; Meng, Xuxu; Qiu, Xiaoyu; Ding, Heyu; Zeng, Rong; Lv, Han; Zhao, Pengfei; Yang, Zhenghan; Gong, Shusheng; Wang, Zhenchang (Frontiers in Neuroscience, 2022)
Objective: Altered cerebral blood flow (CBF) and regional homogeneity (ReHo) have been reported in pulsatile tinnitus (PT) patients. We aimed to explore regional neurovascular coupling changes in PT patients. Materials and methods: Twenty-four right PT patients and 25 sex- and age-matched normal controls were included in this study. All subjects received arterial spin labeling imaging to measure CBF and functional MRI to compute ReHo. CBF/ReHo ratio was used to assess regional neurovascular coupling between the two groups. We also analyzed the correlation between CBF/ReHo ratio and clinical data from the PT patients. Results: PT patients exhibited increased CBF/ReHo ratio in left middle temporal gyrus and right angular gyrus than normal controls, and no decreased CBF/ReHo ratio was found. CBF/ReHo ratio in the left middle temporal gyrus of PT patients was positively correlated with Tinnitus Handicap Inventory score (r = 0.433, p = 0.035). Conclusions: These findings indicated that patients with PT exhibit abnormal neurovascular coupling, which provides new information for understanding the neuropathological mechanisms underlying PT.